Strategic Budget Planning for Financial Management in Primary Schools - Wigiyantini, Meti; Wigiyantini, Nuryaningsih; Rohayanah, Rohayanah; Widiyasuti, Winda; Lestari, Dessy Ari; Suryaman, Maman (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to identify and analyze the planning, implementation, obstacles, and strategies in budget management at primary schools to support quality education improvement. Methodology: Descriptive qualitative method; research subjects: principals, teachers, treasurers, and committee members; data collected via digital five-point Likert scale questionnaire; data analyzed through descriptive narrative based on respondent feedback. Main Findings: Budget planning is participatory and aligned with school vision. Key challenges during implementation include transparency and regulation compliance. Main obstacles: limited budget, low HR capacity, lack of infrastructure. Schools respond with training, IT use, monitoring, and stakeholder involvement to improve accountability and effectiveness. Novelty/Originality of this study: This study highlights integrated strategies combining technology, stakeholder synergy, and capacity development to overcome budget management issues, offering a holistic framework for sustainable education budgeting in primary schools.